Fifty key figures in Latinx and Latin American theatre
1 online resource.
Keywords: "Fifty Key Figures in Latin American and Latinx Theatre is a critical introduction to the most influential and innovative theatre practitioners in the Americas, all of whom have been pioneers in changing the field. The chosen artists bridge political, racial, gender, class, and geographical divides that have traditionally restricted and misrepresented our understanding of Latin American and Latinx theatre while at the same time offering a space to discuss contested nationalities and histories. Each entry considers the artist's or collective's body of work in its historical, cultural, and political context and provides a brief biography and suggestions for further reading. Covering artists from the present day to the 1960s - the emergence of a modern theatre that was concerned with LatinX and Latin American themes rather than mirroring a European approach. A deep and enriching resource for the classroom and individual study, this is the first book that any student of LatinX and Latin American theatre should read"--